Effect of Ultrasonic Surface Rolling Process on the Hot Compression Behavior of Inconel 718 Superalloy at 700 °C - Zhiyan Sun; Shuai Ren; Timin Hu; Bo Li (Nanomaterials, 2019)
A series of hot compression tests at the temperature of 700 °C were applied to study the effect of the ultrasonic surface rolling process (USRP) on the hot compression behavior of Inconel 718 superalloy. The results indicated that the USRP-treated samples exhibited a better ability to withstand axial hot compression than the untreated samples. After the hot compression process, the size of the matrix grains was slightly decreased, and the volume fraction of ultra-fine recrystallized grains in the near-surface regions was increased for the USRP-treated samples. In addition, for USRP-treated samples, a large number of γ″ phases with size less than 100 nm were precipitated within the broadened grain boundaries in the near-surface regions rather than the inner grains. The enhanced ability to withstand axial compression at 700 °C for USRP-treated samples was related to the ultra-fine microstructure induced by USRP, combined with the precipitation of nano-γ″ phases within broadened grain boundaries and the increase of ultra-fine recrystallized grains in the near-surface regions during the hot compression process.